2019
DOI: 10.3390/ijerph16234659
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Novel Antifouling Polysulfone Membrane with in Situ Embedment of Mxene Nanosheets

Abstract: Membrane fouling is still a critical issue for the application of ultrafiltration, which has been widely used in water treatment due to its efficiency and simplicity. In order to improve the antifouling property, a new 2D material MXene was used to fabricate composite ultrafiltration membrane with the approach of in situ embedment during the phase inversion process in this study. Scanning electron microscopy (SEM), atomic force microscopy (AFM), thermogravimetric analysis (TGA), energy dispersive spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 46 publications
3
31
0
Order By: Relevance
“…A cross-flow ultrafiltration test was performed under the same pressure; the permeate was collected at every 20 min for 2 h, a steady flux, J p (L/m 2 •h) for the foulant was obtained over a period of 2 h. After the 2 h filtration process, the membrane was cleaned with RO water and another pure water flux, J w,2 (L/m 2 •h) was conducted for 2 h at 2 bars as the recovery flux. The recovery flux percentage (RFP), reversible fouling (RF) resistance percentage, and irreversible fouling (IF) resistance percentage were defined using Equations ( 6)-( 8), whereas, the total fouling (TF) resistance was used to determine the degree of total flux loss caused during fouling process of the PAP-BM membrane, using the following equations: Shen et al [51]; Vatanpour et al [52]. However, higher RFP indicates a better antifouling property of the membranes.…”
Section: Membrane Antifouling Evaluationmentioning
confidence: 99%
“…A cross-flow ultrafiltration test was performed under the same pressure; the permeate was collected at every 20 min for 2 h, a steady flux, J p (L/m 2 •h) for the foulant was obtained over a period of 2 h. After the 2 h filtration process, the membrane was cleaned with RO water and another pure water flux, J w,2 (L/m 2 •h) was conducted for 2 h at 2 bars as the recovery flux. The recovery flux percentage (RFP), reversible fouling (RF) resistance percentage, and irreversible fouling (IF) resistance percentage were defined using Equations ( 6)-( 8), whereas, the total fouling (TF) resistance was used to determine the degree of total flux loss caused during fouling process of the PAP-BM membrane, using the following equations: Shen et al [51]; Vatanpour et al [52]. However, higher RFP indicates a better antifouling property of the membranes.…”
Section: Membrane Antifouling Evaluationmentioning
confidence: 99%
“…The results in Table indicate that the pure PES membrane has a higher water content of 62.42%, compared to pure PSF having 58.44% water content. However, blending of PES and PSF increased the membrane water content as could be observed with 25% PSF/75% PES membrane with 63.50% water content. This is also evident with the 50% PSF/50% PES which has the highest EWC of 75.17% and a porosity of 60.08% among the membranes with no PVA coat.…”
Section: Resultsmentioning
confidence: 58%
“…Therefore, researchers focus on introducing novel materials to enhance the antifouling property of the membrane to save energy and the operational cost. Recently, MXene-based membranes have been widely used for wastewater treatment, water purification, and desalination applications, as shown in Table 1 [71][72][73][74][75][76][77][78][79][80][81][82]. Initial work by Gogotsi et al [63] demonstrated 2D MXene-based membranes with PVDF supported particular ion separations; for instance, Mg 2+ , Ca 2+ , Li + , Al 3+ , Ni 2+ , Na + , and K + .…”
Section: Water Purification and Desalination Applicationsmentioning
confidence: 99%